1991
DOI: 10.1159/000200706
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged (24-Hour) Manometric Recording of Rectal Contractile Activity in Patients with Slow Transit Constipation

Abstract: A periodic motor activity, named the rectal motor complex, has been recently described in the healthy human rectum. We studied the rectal contractile activity for 24 h by a low compliance manometric system in a group of 10 women with slow transit constipation. Analysis of the 24-hour manometric recordings showed that these subjects: (1) had overall scarce rectal motility; (2) display few rectal motor complexes (average, 3.3 ± 1.3/subject/24 h) which are irregularly distributed over time, and (3) respond weakly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
4

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 17 publications
2
10
4
Order By: Relevance
“…In healthy volunteers, we have shown that the PRMA is confined largely to the rectosigmoid region, often follows a motor event in the more proximal colon, and that there is a distinct circadian rhythm 4 . However, whether this motor activity is altered in patients with functional chronic constipation is controversial 6 , 7 . In one retrospective study, it was claimed that patients with slow transit constipation exhibited fewer PRMA cycles, 7 but there were no control data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy volunteers, we have shown that the PRMA is confined largely to the rectosigmoid region, often follows a motor event in the more proximal colon, and that there is a distinct circadian rhythm 4 . However, whether this motor activity is altered in patients with functional chronic constipation is controversial 6 , 7 . In one retrospective study, it was claimed that patients with slow transit constipation exhibited fewer PRMA cycles, 7 but there were no control data.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether this motor activity is altered in patients with functional chronic constipation is controversial 6 , 7 . In one retrospective study, it was claimed that patients with slow transit constipation exhibited fewer PRMA cycles, 7 but there were no control data. In contrast, another study using solid‐state manometry suggested that patients with slow transit constipation exhibited a tendency for increased incidence of PRMA 6 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that chronically constipated subjects displayed significantly fewer high amplitude propagated contractions and a decreased frequency of urge to defecate,56 suggesting that one important pathophysiological mechanism for constipation may be a decrease in the propulsive ability of the viscus. Other studies have disclosed that patients complaining of slow transit constipation have impaired cyclic rectal activity,57 58 suggesting that these patients have a motor neuropathy.…”
mentioning
confidence: 99%
“…Detubularization reduces the volume-dependent high endoluminal pressure and most of the neobladder contractile activity. The incision for detubularization must be extended as far as the rectosigmoid junction to deactivate the intestinal pacemaker, which has been implicated in colonic pathologies such as constipation and irritable bowel syndrome [4].…”
Section: Discussionmentioning
confidence: 99%